Tomashi Jackson - across the universe - Gale, Nikita 1983-; Kelley, Robin D. G. 1962-; Lash, Miranda Isabel; Munsell, Liz; O'Grady, Megan; Ossei-Mensah, Larry; Whitley, Zoe (Rizzoli Electa, 2024)
"Deeply committed to social justice, artist Tomashi Jackson creates vibrant prints, paintings, videos, textiles, and sculptures that powerfully explore systemic inequities found throughout US history. This is the first book to present the evolution of Jackson's work. Over the course of her career, Jackson has closely investigated specific histories related to cities, lands, and individuals in the United States, with the purpose of revealing how systemic racism and civil rights advocacy have informed America's approach to housing, education, transportation, voter disenfranchisement, police brutality, migration, and agriculture. Inspired by Josef Albers's research on the relativity of color, she employs image layering and the effects of light and perception toward illuminating underrecognized patterns of activism, resistance, oppression, and societal advances. This volume offers an opportunity to look comprehensively at overarching themes and developments in her process by gathering bodies of work in a variety of media created over time and in different locations. Jackson's engaging and nuanced approach to US history situates her as one of the most relevant artists practicing today." --Amazon
Keywords: Jackson, Tomashi -- 1980-; Mixed media; Malerei; Videokunst; Jackson, Tomashi / 1980- / Catalogs; Jackson, Tomashi / 1980- / Exhibitions; Jackson, Tomashi / 1980- / Interviews; 21st century; Art, Modern / 21st century / Exhibitions; Mixed media (Art) / 21st century / Exhibitions; Installations (Art) / 21st century / Exhibitions; Social justice in art / Exhibitions; African American women artists; Art - 21e siècle - Expositions; Technique mixte (Art) - 21e siècle - Expositions; Installations (Art) - 21e siècle - Expositions; Justice sociale dans l'art - Expositions; Femmes artistes noires américaines; ART / General; Art, Modern / https://id.worldcat.org/fast/816615; Mixed media (Art) / https://id.worldcat.org/fast/1765020; Installations (Art) / https://id.worldcat.org/fast/974250; Social justice in art; exhibition catalogs; Exhibition catalogs; Catalogs / https://id.worldcat.org/fast/1423692; Interviews / https://id.worldcat.org/fast/1423832; Catalogues d'exposition; Ausstellungskatalog -- Museum of Contemporary Art -- 14.06.2023-10.09.2023 -- Denver; Ausstellungskatalog -- Institute of Contemporary Art, University of Pennsylvania -- 10.04.2024-02.06.2024 -- Philadelphia; Ausstellungskatalog -- Tufts University Art Galleries -- 30.07.2024-01.12.2024 -- Medord, MA; Ausstellungskatalog -- Institute of Contemporary Art -- 01.2025-05.2025 -- San Francisco; Bildband